2013
DOI: 10.1371/journal.pone.0058574
|View full text |Cite
|
Sign up to set email alerts
|

GLIPR-2 Overexpression in HK-2 Cells Promotes Cell EMT and Migration through ERK1/2 Activation

Abstract: The epithelial-to-mesenchymal transition (EMT) of tubular epithelial cells in the adult kidney is one of the key events in renal interstitial fibrosis. Glioma pathogenesis related-2 (GLIPR-2) has been shown to be up-regulated in proximal tubular cells (PTCs) in the fibrotic kidney. However, the biological function of GLIPR-2 remains unknown. In this study, we found that GLIPR-2 expression is elevated in the kidney tissue samples of patients with diabetic nephropathy (DN). Human proximal renal tubular epithelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…GLIPR2 and FAM129B were both assigned to the differentiation cluster (Fig. D) and have recently been identified as direct transcriptional targets of ERK signaling in HK‐2 cells and human melanoma cells, respectively . This suggests that cells upregulate FGF/MAPK signaling by shutting down negative feedback components during PrE differentiation, thereby ensuring the continuous FGF/MAPK signaling required for PrE differentiation .…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…GLIPR2 and FAM129B were both assigned to the differentiation cluster (Fig. D) and have recently been identified as direct transcriptional targets of ERK signaling in HK‐2 cells and human melanoma cells, respectively . This suggests that cells upregulate FGF/MAPK signaling by shutting down negative feedback components during PrE differentiation, thereby ensuring the continuous FGF/MAPK signaling required for PrE differentiation .…”
Section: Resultsmentioning
confidence: 81%
“…E) along the differentiation time‐course, although phosphorylation levels in established XEN cell lines were lower than after 72 hours of doxycycline exposure. Both GLIPR2 and FAM129B have been implicated in endowing cells with increased motility , suggesting that they provide a link between the dependence of PrE differentiation on FGF/MAPK signaling and acquisition of a motile phenotype upon differentiation along this lineage.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that GLIPR-2 is abundantly increased in PTCs during kidney fibrogenesis [14]. Further more, our previous results demonstrated that GLIPR-2 contributes significantly to EMT in HK-2 cells which has been classified as type 2 EMT [15]. However, whether GLIPR-2 could induce type 3 EMT occured in carcinogenesis needs further investigation.…”
Section: Introductionmentioning
confidence: 80%
“…Although it is implicated in human brain tumor growth and kidney fibrosis, the precise biological activity remains unknown [14], [20]. Our previous studies have shown that GLIPR-2 was highly expressed in proximal renal tubular epithelial cells in diabetic nephropathy and overexpression of GLIPR-2 in HK-2 cells promotes EMT in vitro via ERK1/2 signaling pathway, which was classified as type 2 EMT involved in renal fibrosis [15]. Therefore, we hypothesized that GLIPR-2 is elevated in the EMT process in carcinogenesis (type 3 EMT) and involved in tumor invasion and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Glipr2 is a signaling molecule, which has not been well-characterized, but is upregulated in sciatic nerve injury from experimental diabetes (Zhang et al, 2015). Glipr2 is involved in transition of epithelial to mesenchymal cells by way of epidermal growth factor signaling pathways (Huang et al, 2013), which are also known to be involved in recovery from muscle injury. Dyrk2 encodes a tyrosine kinase, which negatively regulates growth of cardiac myocytes (Weiss et al, 2013), and the reduced expression of Dyrk2 in EAMG would be expected to promote recovery from injury.…”
Section: Discussionmentioning
confidence: 99%